(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article describes the methodology of teaching a foreign language, the history of its development as a science, the types of contemporary methods used in the methodology of teaching a foreign language and their use.